Difficult knowledge and history education. (27th May 2022) - Stoddard, Jeremy
ABSTRACT: Over the past decade, scholars from a variety of epistemological and theoretical backgrounds have begun to engage more deeply with history as a form of difficult knowledge. It is difficult to comprehend and can be traumatic for different groups for different reasons. History as a school subject has largely been used as a tool of hegemony by presenting nationalistic dominant narratives that can marginalise and oppress students from minoritized populations. This academic work has been primarily theoretical, but small case studies of empirical analysis of how teachers and students engage with history as difficult knowledge have emerged to inform practice. This article draws from this body of work – grounded in theories of memory and identity, critical socio-cultural approaches, and psychoanalytic and trauma-informed analysis – to explore key considerations for informing teaching and learning difficult histories. These include the relationship between teacher moral commitments and engagement with or resistance to difficult histories; the role of emotion and unsettling nature of difficult knowledge, and making assumptions about what representations of historic social trauma are or are not traumatising for young people. These considerations have implications for teaching and teacher education.